Intelligent Nanodelivery System‐Generated 1O2 Mediates Tumor Vessel Normalization by Activating Endothelial TRPV4‐eNOS Signaling. Issue 17 (25th March 2022) - Zhang, Shuaiqiang; Li, Yuanhao; Li, Zhuoyue; Wang, Guangxue; Liao, Ai; Wang, Jingru; Li, Hui; Guo, Zefeng; Cheng, Boyang; Zhang, Xuan
Abstract: Tumor microenvironment (TME)‐responsive intelligent photodynamic therapy (PDT) systems have attracted increasing interest in anticancer therapy, due to their potential to address significant and unsatisfactory therapeutic issues, such as limited tissue penetration, inevitable normal tissue damage, and excessive impaired vessels. Here, an H2 O2 ‐triggered intelligent LCL/ZnO PDT nanodelivery system is elaborately designed. LCL/ZnO can selectively regulate tumor‐derived endothelial cells (TECs) and specifically kill tumor cells, by responding to different H2 O2 gradients in TECs and tumor cells. The LCL/ZnO is able to normalize tumor vessels, thereby resulting in decreased metastases, and ameliorating the immunosuppressive TME. Further analysis demonstrates that singlet oxygen ( 1 O2 )‐activated transient receptor potential vanilloid‐4‐endothelial nitric oxide synthase signals generated in TECs by LCL/ZnO induce tumor vascular normalization, which is identified as a novel mechanism contributing to the increased ability of PDT to promote cancer therapy. In conclusion, designing an intelligent PDT nanodelivery system response to the TME, that includes both selective TECs regulation and specific tumor‐killing, will facilitate the development of effective interventions for future clinical applications. Abstract : An H2 O2 ‐triggered intelligent LCL/ZnO photodynamic therapy nanodelivery system is elaborately designed by an amphiphilic LCL self‐assembled on the surface of hydrophobic ZnO nanozymes. LCL/ZnO can selectively regulate transient receptor potential vanilloid‐4‐endothelial nitric oxide synthase signals in tumor‐derived endothelial cells (TECs) inducing tumor vascular normalization and specifically kill tumor cells, by responding to different H2 O2 gradients in TECs and tumor cells.